Food justice accompaniment research: theory and social praxis in West Virginia - Wilson, Bradley R.; Lohnes, Joshua (Frontiers in Sustainable Food Systems, 2023)
Over the past three decades West Virginians have experienced a deepening economic crisis. Divestment in coal and manufacturing has resulted in widespread unemployment, state, county and municipal revenue losses, and cascading effects on social services, households, livelihoods and community life. For ten years, FJL has conducted ethnographic research, coordinated cooperative experiments and built pedagogical tools to democratize knowledge about West Virginia’s food system amidst this crisis. Working in a so-called red state, we have fostered conversations about food justice with rural, often socially conservative communities, and have worked to raise up human resources for meaningful community-led food justice organizing in Central Appalachia. In this paper we consider the long accompaniment process with community partners and the effects of this experience on the evolution of research questions and actions.